3-D motion correction for volumetric super-resolution ultrasound (SR-US) imaging - Harput,S; Christensen-Jeffries,K; Brown,J; Zhu,J; Zhang,G; Eckersley,RJ; Dunsby,C; Tang,M (IEEE, 2018)
Motion during image acquisition can cause imagedegradation in all medical imaging modalities. This is particularlyrelevant in 2-D ultrasound imaging, since out-of-plane motioncan only be compensated for movements smaller than elevationalbeamwidth of the transducer. Localization based super-resolutionimaging creates even a more challenging motion correction taskdue to the requirement of a high number of acquisitions to forma single super-resolved frame.In this study, an extension of two-stage motion correctionmethod is proposed for 3-D motion correction. Motion estimationwas performed on high volumetric rate ultrasound acquisitionswith a handheld probe. The capability of the proposed methodwas demonstrated with a 3-D microvascular flow simulation tocompensate for handheld probe motion. Results showed that two-stage motion correction method reduced the average localizationerror from 136 to 18μm.